Ateism or Agnosticism?: Bertrand Russell’s Preference - Yıldırım, Tamer (Hamdi BRAVO, 2011)
In this article, I am going to discuss definition of agnosticism. In generally agnosticism is the belief that man cannot know whether or not God exists. The great British philosopher and mathematician Bertrand Russell’s (1872–1970) approach to religion will be evaluated in the context of his works. And in this article it will be tried to exposed that Russell is not an atheist,but only an agnostic

Bu makalede agnostisizmin tanımı tartışılacaktır. Genelde agnostikler, insanın Tanrı’nın var olup olmadığını bilemeyeceğine inanır. Bu anlamda İngiliz filozof ve matematikçi Bertrand Russell’ın (1872–1970) eserlerinden hareketle onun dine yaklaşım tarzı ele alınacak ve Russell’ın bir ateist değil daha ziyade bir agnostik olduğu gösterilecektir
ATEİZM Mİ AGNOSTİSİZM Mİ? BERTRAND RUSSELL’IN TERCİHİ